CORPORATE SOCIAL BUSINESS POLICY: APPROACHES AND MODERN DEVELOPMENT TRENDS - E. Smirnova; S. Mitrofanova (Вестник Северо-Кавказского федерального университета)
The article is devoted to the classic approaches of corporate social responsibility of business -corporate egoism, corporate altruism, sensible (enlightened) egoism, and experience in implementing corporate social policy of business in accordance with one of them. The main trends in the development of external social policy and the participation of business in solving social problems of society are considered in the example of the flagships of the telecommunications business - PJSC VimpelCom, PJSC MegaFon and PJSC Mobile TeleSystems. Among the most relevant areas of corporate social policy are assistive technologies, M charity service, social projects of various kinds, and corporate volunteering.